The Psychology of Cultural Dynamics What Is It, What Do We Know, and What Is Yet to Be Known?. [article]. - Kashima, Yoshihisa
The psychology of cultural dynamics is the psychological investigation of the formation, maintenance, and transformation of culture over time. This article maps out the terrain, reviews the existing literature, and points out potential future directions of this research. It is divided into three parts. The first part focuses on micro-cultural dynamics, which refers to the social and psychological processes that contribute to the dissemination and retention of cultural information. The second part, on micro?macro dynamics, investigates how micro-level processes give rise to macro-cultural dynamics. The third part focuses on macro-cultural dynamics, referring to the distribution and long-term trends involving cultural information in a population, which in turn enable and constrain the micro-level processes. We conclude the review with a consideration of future directions, suggesting behavior change research as translational research on cultural dynamics. -- (from the author)